The Javeriana Cali’ Strategic Plan for the Sustainable Management: An Example of How to Implement, Disseminate and Evaluate Sustainability Policies - Isabella Tello; Jose Alejandro Aguilar (Journal of Sustainability Perspectives, 2024)
In order to organize the multiple actions the Universidad Javeriana had been developing for the sustainable management of its campus, a strategic plan was structured. The plan is structured in five major programs: water resources, energy, biodiversity, recycling and reduction of CO2 emissions. For the definition of these five programs we were inspired by the contributions of the thematic structure of Green Metrics, the recommendations of the Encyclical Laudato Si and the SDGs. In turn, each program is broken down into sub-programs, projects and sub-projects. Each program also includes cross-cutting strategies articulated in sub-programs which are broken down into research projects, semester projects, graduate work and theses. Also, sub-programs for disseminating initiatives and entrepreneurship are considered. The planning instrument is taken to the detail of operational planning, using the Gantt Chart. A team coordinates the coordination of the different programs and meets weekly to review its progress. The plan was presented and approved to the University's Steering Committee, and the document has been incorporated into the University's Strategic Plan. It is also being used to link professors from civil engineering, electronics and architecture careers who invite students to carry out semester or degree work on topics that strengthen campus execution.